Tyrosine Kinase Inhibitors Could Be Effective Against Non-small Cell Lung Cancer Brain Metastases Harboring Uncommon EGFR Mutations - Ma, Chunhua; Zhang, Juncheng; Tang, Dongjiang; Ye, Xin; Li, Jing; Mu, Ning; Li, Zhi; Liu, Renzhong; Xiang, Liang; Huang, Chuoji; Jiang, Rong (Frontiers in Oncology, 2020)
Background: The significance of uncommon epidermal growth factor receptor (EGFR) mutations in patients with non-small cell lung cancer (NSCLC) and brain metastasis (BM) remains unclear. Cerebrospinal fluid (CSF) liquid biopsy is a novel tool for assessing EGFR mutations in BM. This study aimed to evaluate the EGFR mutations in patients with NSCLC and newly diagnosed BM and to examine the effect of EGFR tyrosine kinase inhibitors (TKI) on BM harboring CSF-tested uncommon EGFR mutations. Methods: This was a prospective study of 21 patients with NSCLC and BM diagnosed between 04/2018 and 01/2019. CSF was obtained to detect the BM EGFR mutations by next-generation sequencing. BM characteristics at magnetic resonance imaging (MRI) and EGFR-TKI response were examined. Results: Of 21 patients with NSCLC, 10 (47.6%) had leptomeningeal metastasis (LM), while 11 (52.4%) had brain parenchymal metastasis (BPM); 13 (61.9%) had confirmed EGFR mutation-positive primary tumors. The uncommon mutation rate in CSF ctDNA was 33.3% (7/21). Among those with EGFR mutation-positive primary tumors, the rate of uncommon EGFR mutations in CSF was 53.8% (7/13). Uncommon EGFR mutations were more common in patients with LM than in patients with PBM (6/11, 54.5% vs. 1/10, 10%), and included G719A, L861Q, L703P, and G575R. TKI was effective for four patients with BMs harboring uncommon EGFR mutations. Conclusion: In patients with NSCLC and LM, the rate of uncommon EGFR mutation was high. The BMs with uncommon EGFR mutations seem to respond to EGFR-TKI treatment. CSF liquid biopsy could reveal the EGFR genetic profile of the BM and help guide treatment using small-molecule TKI.